In Situ 3D-µ-Tomography on Particle-Reinforced Light Metal Matrix Composite Materials under Creep Conditions - Bettina Camin; Lennart Hansen (Metals, 2020)
In transportation light metal matrix composites (L-MMCs) are used increasingly due to their improved creep resistance even at higher application temperatures. Therefore, the creep behavior and failure mechanisms of creep loaded particle reinforced L-MMCs have been investigated intensively. Until now, creep damage analyses are usually performed ex situ by means of interrupted creep experiments. However, ex situ methods do not provide sufficient information about the evolution of creep damage. Hence, in situ synchrotron X-ray 3D-µ-tomography investigations were carried out enabling time and space resolved studies of the damage mechanisms in particle-reinforced titanium- and aluminum-based metal matrix composites (MMCs) during creep. The 3D-data were visualized and existing models were applied, specifying the phenomenology of the damage in the early and late creep stages. During the early stages of creep, the damage is determined by surface diffusion in the matrix or reinforcement fracture, both evolving proportionally to the macroscopic creep curve. In the late creep stages the damage mechanisms are quite different: In the Al-MMC, the identified mechanisms persist proportional to creep strain. In contrast, in the titanium-MMC, a changeover to the mechanism of dislocation creep evolving super-proportionally to creep strain occurs.